The relationship between motor function, cognition, independence and quality of life in myelomeningocele patients - Luz, Carolina Lundberg; Moura, Maria Clara Drummond Soares de; Becker, Karine Kyomi; Teixeira, Rosani Aparecida Antunes; Voos, Mariana Callil; Hasue, Renata Hydee (Arquivos de Neuro-Psiquiatria, 2017)
Motor function, cognition, functional independence and quality of life have been described in myelomeningocele patients, but no study has investigated their relationships. We aimed to investigate the relationships between motor function, cognition, functional independence, quality of life, age, and lesion level in myelomeningocele patients, and investigate the influence of hydrocephalus on these variables. We assessed 47 patients with the Gross Motor Function Measure (motor function), Raven’s Colored Progressive Matrices (cognition), Pediatric Evaluation of Disability Inventory (functional independence) and the Autoquestionnaire Qualité de vie Enfant Imagé (quality of life). Spearman’s correlation tests determined relationships between the variables. The Friedman ANOVAs determined the influence of hydrocephalus. Motor function was strongly related to mobility and lesion level, and moderately related to cognition, self-care and social function. Cognition and quality of life were moderately related to functional independence. Age correlated moderately with functional independence and quality of life. Hydrocephalus resulted in poorer motor/cognitive outcomes and lower functional independence.
Keywords: meningomyelocele; quality of life; cognition